Pengembangan Wisata Budaya di Taman Nasional Wasur Berbasis Kearifan Lokal - Numberi, Gerdha K.I.; Sanggenafa, Christine O.I.; de Fretes, Diego R. (Universitas Cenderawasih, 2022)
This research, which is located in Merauke Regency, aims to identify two things; first, tracing the framework for developing tourist destinations based on local wisdom of the Marori Tribe, second, finding the correlation of local wisdom of the Marori Tribe which was adopted as a development of culture-based tourism in the Wasur National Park area, Merauke Regency. This study uses a qualitative descriptive method with a case study approach. Data was collected by means of interviews, literature studies, and documentation as a complement. The data analysis technique uses data reduction, data display, as well as drawing conclusions and data verification (conclusion drawing and data verification). The results of this study state that the development of cultural tourism based on local wisdom carried out by the Marori Tribe in Wasur National Park has included all components in the framework of developing tourist destinations, namely attractions, accessibility, amenities, ancillary services, and institutions